Attitude 2007 : the house of human beings - authentically blessed jubilance - CAMK (Contemporary Art Museum), Kumamoto (Kumamoto : CAMK (Contemporary Art Museum) Kumamoto, 2007)
Abe, Kaoru ; Akuta, Masahiko ; Araki, Nobuyoshi ; Ayukawa, Makoto ; Boyadjiev, Luchezar ; Chicago, Judy ; Geismar, Jarg ; Haniya, Yutaka ; Hijikata, Tatsumi ; Hori, Kosai ; Ishida, Sumio ; Katashima, Norio ; Kawashima, Kiyoshi ; Kinoshita, Susumu ; Libera, Zbigniew ; Mikhailov, Boris ; Nakayama, Daisuke ; Nakayama, Setsuo ; Rimsakul, Porntaweesak ; Sokov, Leonid ; Todosijevic, Rasa Dragoljub ; Tsuji, Ayako ; Woodman, Donald ; Yamada, Shinichi ; Yamamoto, Tadasu ; Yanagi Miwa
Engels, Japans
Exhibition. Attitude 2007. CAMK (Contemporary Art Museum) Kumamoto. 2007-07-21. 2007-10-14
boek